2016
DOI: 10.1177/0898264315614570
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hearing Loss and Loneliness in Older Adults

Abstract: Younger age and greater hearing loss are independently associated with higher levels of loneliness in older adults presenting to clinic for hearing loss treatment. Further studies needed to determine whether hearing treatment can reduce loneliness in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 30 publications
4
87
2
Order By: Relevance
“…The association of hearing loss and loneliness has been previously documented in this population, as well as a population aged 18 to 30 years . This is consistent with other research, which has demonstrated an association between hearing loss and depression, social isolation, and anxiety .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The association of hearing loss and loneliness has been previously documented in this population, as well as a population aged 18 to 30 years . This is consistent with other research, which has demonstrated an association between hearing loss and depression, social isolation, and anxiety .…”
Section: Discussionsupporting
confidence: 91%
“…Individuals with hearing loss have been shown to have poorer health outcomes, including decreased cognitive function, quality of life, and mobility . The association between hearing impairment (HI) and loneliness has been reported in both younger and older adults . Hearing aids (HA) and cochlear implants (CI) are the most common devices used for the treatment of hearing loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also spend less time out of the home, are at higher risk for withdrawal from leisure activities (Mikkola, Polku, Portegijs, Rantakokko, Tsai, et al, 2015) and are just generally at higher risk for social inactivity (Crews & Campbell, 2004;Mikkola, Polku, Portegijs, Rantakokko, Tsai, et al, 2015;Simonsick, Kasper, & Phillips, 1998;Viljanen, Törmäkangas, Vestergaard, & Andersen-Ranberg, 2014). In addition, studies have shown that poor hearing is associated with loneliness (Pronk, Deeg, & Kramer, 2013;Sung, Li, Blake, Betz, & Lin, 2015) and social isolation (Mick, Kawachi, & Lin, 2014;Mick & Pichora-Fuller, 2016). However, note that diverging results exist (Mick et al, 2014;Mick & Pichora-Fuller, 2016;Yamada, Nishiwaki, Michikawa, & Takebayashi, 2012), possibly caused by inconsistencies in hearing and social participation measures, and differences in study samples.…”
Section: Interaction Of Hearing Impairment Balance and Social Particmentioning
confidence: 78%
“…Elderly people who are hard of hearing have problems with communication and report a decrease in the quality of life and physical and cognitive activities [Bainbridge and Wallhagen, 2014]. Multiple studies have shown that hearing loss not only incapacitates the ability to communicate, but also that it is positively associated with depression, somatization disorder, and loneliness in older adults [Ciorba et al, 2012;Sung et al, 2015]. In addition, hearing loss was found to be associated with an increased risk of developing dementia [Fortunato et al, 2016;Lin et al, 2011;Peracino, 2014].…”
Section: Introductionmentioning
confidence: 99%